Answer:
A(b) =
![(1)/(2) (b^2 + 3b)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vvzp6vl47orw6p0ckvmxj3rjwjcxkbzpxu.png)
Explanation:
Given: Height of the triangle is 3 units more than the base.
Let "b" be the base of the triangle.
So, h = b + 3
Area of a triangle A =
![(1)/(2) base * height](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9cwv7h6ywdtk1u1s7x8lhyjdjovzurzyp0.png)
Now plug in h = b +3 in the above area of formula, we get
A(b) =
![(1)/(2) b*(b + 3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/190rxpsgeez6vgad6uupoe1oso40ow06r9.png)
Now we can multiply b and (b + 3), we get
A(b) =
![(1)/(2) (b^2 + 3b)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vvzp6vl47orw6p0ckvmxj3rjwjcxkbzpxu.png)
Therefore, the answer is A(b) =
![(1)/(2) (b^2 + 3b)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vvzp6vl47orw6p0ckvmxj3rjwjcxkbzpxu.png)